An experiment on donations, personal stories, and bad luck - Ronen Bar-El; Limor Hatsor; Avichai Snir (Bar-Ilan University, Department of Economics, 2023)
We conducted two fundraising experiments to study the effects (1) of compassion towards the beneficiary, and (2) of giving participants an opportunity to attribute small donations to luck. We find that exposing the participants to a plea to help the beneficiary increases the average donation. Giving participants an opportunity to attribute small donations to luck decreases the average donation. We find that in our setting, the latter effect dominates.
Keywords: C91; D64; D91; L31; 330; Charity; Donations; Experiment; Fundraising; Expressive Behavior; lottery